NOTES ON STOMATOPOD CRUSTACEA FROM SERIBU ISLANDS AND ADJACENT WATERS WITH A DESCRIPTION OF A NEW SPECIES - Moosa, M. Kasim (Marine Research in Indonesia, 1975)
The stomatopod fauna of Seribu Islands, Jakarta Bay, and adjacent waters is still poorly known. This study reveals the existence of 30 species in this area. A new species belonging to Oratosquilla is described. Records of distribution for those species are based on the material collected from thisÂ  area only.